Estudio técnico y económico para el uso de materiales reciclados de cartón, papel y madera en la producción de cajas para empaque de babaco y tomate riñón - Acosta Núñez, Bryan Alberto (2021)
In Ecuador there are 180 hectares planted with babaco, which is why, according to Jorge Fabara, a fruit technician, the province of Tungurahua ranks first with 60% of national production and kidney tomato cultivation in the central zone of the inter-Andean region. , from the province of Tungurahua, covers 70% (INIAP, 2005). Through visual evaluation it has been seen that so far one of the areas with the highest production of babaco and kidney tomato at the national level, such as the cantons of Patate, Baños and Pelileo in the province of Tungurahua, do not have a cardboard box packing company. For these foods, this has caused the producers, as a first option, to have to go to another city to buy provisional cartons, which are for banana and apple packaging, causing in most cases, loss of time due to transfers and costs a little. more than high after this analysis, a good alternative to the creation of cardboard boxes for packing babaco and kidney tomato is seen. The purpose of the packaging system is to facilitate the collection, packing and classification of merchandise for shipment, protecting them from physical and environmental risks during storage and transportation, its ultimate function is to motivate the consumer to purchase it, guaranteeing that it is in the same conditions of quality that it had at the time of its collection or manufacture.